Pengembangan Media Pembelajaran Booklet Berbasis Etnobotani Sayuran Lokal Di Kecamatan Semitau: (Development of a Booklet-Based Learning Media on Local Vegetable Ethnobotany in Semitau District) - Hadini, Dayang Nur; Amri, Ahmad Faisal; Rahayu, Hanum Mukti (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2025)
This study aims to develop an instructional medium in the form of a booklet based on the ethnobotany of local vegetables found in Semitau District, to be used as a learning resource on biodiversity for tenth-grade high school students. The background of this research is rooted in the lack of integration of local potential into the biology learning process in schools, which has resulted in students’ limited understanding of the importance of conserving biological resources in their surroundings. The research employed a Research and Development (R&D) approach using the 4-D model, which was modified into a 3-D model consisting of define, design, and develop stages. The research procedure included needs analysis of teachers and students, identification of local vegetable species, and the design and validation of the booklet. Validation results by experts indicated that the developed booklet had a high level of validity, with an average score of 87.22% from media experts, 84.44% from material experts, and 78.44% from language experts. Trials conducted with students on a small and large scale showed highly positive responses, with percentages of 84.61% and 87.72%,respectively. Therefore, the ethnobotany-based local vegetable booklet developed in this study is considered highly valid and feasible to be used as a learning medium for biodiversity material. Key words: Booklet, Ethnobotany, Local Vegetables, Biodiversity, Learning Media